Replicate Measurements of Haemoglobin Mass during a Single Day are Feasible and Precise - Naef, N.; Steiner, T.; Wehrlin, J. P. (International Journal of Sports Medicine, 2015)
Duplicate haemoglobin mass (Hbmass) measurements are recommended before and after altitude training sojourns to identify individual adaptations in athletes with a high level of certainty. Duplicate measurements reduce typical error (TE) and disclose measurement outliers, but are usually made on separate days, which is not a practical protocol for routine services in elite sport settings. The aim of this study was therefore to investigate whether it is safe (carboxyhaemoglobin<10%) to measure Hbmass twice on the same day and to compare TE with measurements made on separate days. 18 healthy men completed 3 different procedures to measure Hbmass twice a day with the carbon monoxide rebreathing method: A (Hbmass measured twice within 6 h), B (dito A, combined with 1 h of hyperoxic training between the tests), C (dito B, within 2 h). First Hbmass measurements of the 3 test days served as procedure D. Carboxyhaemoglobin did not exceed 10% in any procedure. TE and confidence limits for procedures A, B, C and D were 1.4% (1.0–2.1%), 1.1% (0.8–1.7%), 1.3% (1.0–2.0%) and 1.5% (1.2–2.1%), respectively. Duplicate measurements of Hbmass on the same day are feasible and show TE similar to triplicate measurements on separate days.
Keywords: CO-rebreathing method; altitude training; athletes; Hbmass; reproducibility; technical error